Integrated approach on solar drying, pilot convective drying and microstructural changes - Ramos, Inês N. (2010)
Solar drying of foods is an old technique, still used nowadays. Nevertheless, the mathematical approach of the complex phenomena involved is not completely integrated. Drawbacks appear in modelling heat transport, specially related to the huge variability of meteorological factors. The great dependence of the heat and mass transfer model parameters on water content is also frequently forgotten. Macroscopic changes (e.g. shrinkage) that occur during drying processes, are usually not considered in mass transfer equations, also affecting the predictive ability of the models. The objective of this work was to develop the mathematical basis and considerations for integrating heat and mass transfer phenomena, taking into consideration macroscopic changes and their correlation to changes at microscopic level (e.g. cellular shrinkage), that might occur during solar drying of grapes.